2016
DOI: 10.7205/milmed-d-15-00184
|View full text |Cite
|
Sign up to set email alerts
|

Military Occupations Most Affected by Head/Sensory Injuries and the Potential Job Impact of Those Injuries

Abstract: Head and sensory injuries disproportionately affect certain military occupations. Relatively few injuries disrupt combat-related abilities that are job critical (e.g., firearms operation) and job specific (e.g., Artillery gunnery problems); these should be the focus of efforts to improve rehabilitation and RTD outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…The detection of a difference in tinnitus shown in these results suggests that this method for discovery was effective. In addition, this finding was consistent with a previous epidemiological study that showed association between combat arms MOSs (infantry) and risk for auditory injury (17), although that study approach used injury codes to search for MOS association rather than the approach presented here, using MOS categories to evaluate differences in injury rates. To further assess the potential for risk from occupational exposure to blast, following studies could explore annual hearing assessment results in conjunction with MOS as an additional proxy for longitudinal exposure to blast.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The detection of a difference in tinnitus shown in these results suggests that this method for discovery was effective. In addition, this finding was consistent with a previous epidemiological study that showed association between combat arms MOSs (infantry) and risk for auditory injury (17), although that study approach used injury codes to search for MOS association rather than the approach presented here, using MOS categories to evaluate differences in injury rates. To further assess the potential for risk from occupational exposure to blast, following studies could explore annual hearing assessment results in conjunction with MOS as an additional proxy for longitudinal exposure to blast.…”
Section: Discussionsupporting
confidence: 90%
“…Professional communities exposed to blast in their occupational roles may have exposures during tactical operations, but they will all have exposures during routine training, for acquiring needed skills as well as maintaining those skills over time. Occupation-based estimates of risk from exposure history have been revealed for military occupational specialties (MOSs) in previous studies ( 17 19 ) and could serve to prevent injury as has been recommended for contact sports ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sensory impairments affect military service members readiness for deployment (169), job performance (170), and quality of life (171). The blast-related mTBI participants in these studies had a 100% report rate for some level of hearing disturbance immediately following the blast and symptoms persisted upwards of 6 months post-deployment (87,88,114,117,138).…”
Section: Discussionmentioning
confidence: 97%
“…Survivors might experience similar benefit and outcomes from rehabilitation compared with survivors of nonpenetrating injuries, 13 but more data about risk factors and trajectories of recovery are needed, especially to determine whether specialized prevention and intervention approaches may be warranted. Available literature on penetrating TBIs, and particularly FI-related TBI, however, consists of small sample sizes or case studies, [14][15][16] targets specific populations (eg, military service members), 17 and/or focuses only on descriptive sociodemographic data. 12,13,18,19 More data about injury and clinical characteristics and outcomes among civilian FIrelated TBI survivors are needed to develop appropriate prevention and rehabilitation programs for these individuals, particularly given the unique issues surrounding such injuries.…”
mentioning
confidence: 99%